Perubahan Penggunaan Lahan dan Karakteristik Hidrologi DAS Citarum Hulu - Muhammad Yahya Fadhil; Yayat Hidayat; Kukuh Murtilaksono; Dwi Putro Tejo Baskoro (Institut Pertanian Bogor, 2021)
The Citarum watershed is one of the priority watersheds due to problems of critical land, flooding, erosion, and sedimentation which continue to increase every year. As the main catchment area that contributes to maintaining the availability of water resources, the upstream Citarum watershed continues to experience a reduction in forest and an increase in built-up land. A research aimed to analyze land use changes to the hydrological characteristics was carried out at the Watershed. The methods used include interpretation of SPOT image data, analysis of land use changes, and determining the values of KRA and KAT. The results of the analysis of land use change conditions in 2009-2018 saw a reduction in forest area (-5.5%), rice fields (-17.4%), and shrubs (-60.8%). Land use increased in built up land (39.7%), dry land agriculture (13%), plantations (6.4%), and open land (95.5%). The highest discharge occurred in 2010 at 606,3 m3/second and the lowest discharge in 2012 was 4,3 m3/second. The KRA and KAT values of the Upper Citarum watershed were moderate and very high. The multiple linear regression model of the relationship between land use changes that affect river flow fluctuations is Y = 2380.5 + 0.9 rainfall -206.5 forest + 6.1 build-up area -31.8 dryland agriculture + e. Other factors that influence the increase in river discharge are the slope of land slopes, rainfall patterns, and inadequate land use methods. Keywords: hydrological characteristics, landuse change, Upper Citarum watershed